Effects of NT5C2 Germline Variants on 6‐Mecaptopurine Metabolism in Children With Acute Lymphoblastic Leukemia. Issue 6 (24th November 2020) - Jiang, Chuang; Yang, Wenjian; Moriyama, Takaya; Liu, Chengcheng; Smith, Colton; Yang, Wentao; Qian, Maoxiang; Li, Ziping; Tulstrup, Morten; Schmiegelow, Kjeld; Crews, Kristine R.; Zhang, Hui; et al.
Abstract : 6‐mercaptopurine (6‐MP) is widely used in the treatment of acute lymphoblastic leukemia (ALL), and its cytotoxicity is primarily mediated by thioguanine nucleotide (TGN) metabolites. A recent genomewide association study has identified germline polymorphisms (e.g., rs72846714) in the NT5C2 gene associated with 6‐MP metabolism in patients with ALL. However, the full spectrum of genetic variation in NT5C2 is unclear and its impact on 6‐MP drug activation has not been comprehensively examined. To this end, we performed targeted sequencing of NT5C2 in 588 children with ALL and identified 121 single nucleotide polymorphisms nominally associated with erythrocyte TGN during 6‐MP treatment ( P < 0.05). Of these, 61 variants were validated in a replication cohort of 372 children with ALL. After considering linkage disequilibrium and multivariate analysis, we confirmed two clusters of variants, represented by rs72846714 and rs58700372, that independently affected 6‐MP metabolism. Functional studies showed that rs58700372 directly altered the activity of an intronic enhancer, with the variant allele linked to higher transcription activity and reduced 6‐MP metabolism (lower TGN). By contrast, rs72846714 was not located in a regulatory element and instead its association signal was explained by linkage disequilibrium with a proximal functional variant rs12256506 that activated NT5C2 transcription in‐ cis . Our results indicated that NT5C2 germline variation significantly contributes to interpatient variability in thiopurine drug disposition.